2011
DOI: 10.1044/0161-1461(2010/09-0067)
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and Predicting Outcomes of Communication Delays in Infants and Toddlers: Implications for Clinical Practice

Abstract: Extant literature suggests that EI makes a critical difference in the developmental course of communication as well as in other learning domains for children with a variety of established conditions. The literature also provides guidance to SLPs who must evaluate and weigh risk factors for children with less clear eligibility for services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 71 publications
(71 reference statements)
6
55
0
6
Order By: Relevance
“…This has shown that prediction of language outcome is poor if reliance is only placed on expressive language measures, especially when using early parent-report measures of language development Feldman et al, 2005;Henrichs et al, 2011;Westerlund et al, 2006). There is a need for multifactorial predictive risk models that include a wide range of verbal and nonverbal factors (Desmarais et al, 2008;Ellis & Thal, 2008;Hawa & Spanoudis, 2014;Olswang, Rodriguez, & Timler, 1998;Paul & Roth, 2011;Zambrana, Pons, Eadie, & Ystrom, 2014). To date, numerous perinatal (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has shown that prediction of language outcome is poor if reliance is only placed on expressive language measures, especially when using early parent-report measures of language development Feldman et al, 2005;Henrichs et al, 2011;Westerlund et al, 2006). There is a need for multifactorial predictive risk models that include a wide range of verbal and nonverbal factors (Desmarais et al, 2008;Ellis & Thal, 2008;Hawa & Spanoudis, 2014;Olswang, Rodriguez, & Timler, 1998;Paul & Roth, 2011;Zambrana, Pons, Eadie, & Ystrom, 2014). To date, numerous perinatal (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of LTs move into the typical range on standardised language measures during the preschool period, but a subset continues with language impairments throughout the school years (Domsch et al, 2012;Ellis & Thal, 2008;Henrichs et al, 2011;Moyle, Weismer, Evans, & Lindstrom, 2007;Paul & Roth, 2011;Rescorla, 2011;Westerlund, Berglund, & Eriksson, 2006). LTs do not constitute a homogeneous group but present with varied profiles of language and/or social communication skills and deficits which change over time: some present with expressive language problems only, whereas others also evidence limited receptive language and/or social communication skills that border on Autism Spectrum Disorders (ASD) (Desmarais, Sylvestre, Meyer, Bairati, & Rouleau, 2008;Ellis & Thal, 2008;Hawa & Spanoudis, 2014;Paul & Ellis Weismer, 2013;Paul & Roth, 2011). But although some LTs and young children with ASD share common features, it is important to acknowledge that not all late-talking toddlers with social communication deficits meet diagnostic criteria for ASD.…”
Section: Introductionmentioning
confidence: 99%
“…10−15% lastest ei arene kõne ootus päraselt (Desmarais, Sylvestre, Meyer, Bairati, & Rouleau, 2008;Paul & Roth, 2011). Kõne arengu mahajäämust märgitakse alates 2 aasta vanusest, kui eeldatud lihtsaid lauseid pole lapse kõnesse ilmunud.…”
Section: Sissejuhatusunclassified
“…Üldi selt peetakse selleks vanuseks 5 aastat (Paul & Roth, 2011;Rescorla, 2011). Kõnehilistusega lapsed, kes 5aastaselt on kõne arengu näitajate poolest veel EK lastest märgatavalt nõrgemad, on tõenäoliselt juba raskema ja püsivama puudega -nn spetsiifilise kõnearengupuudega (vt Hallap, Padrik, & Raudik, 2014;Padrik, 2014).…”
Section: Kõne Arengu Hilistuse Ehk Peetusega Lapsedunclassified
See 1 more Smart Citation